PEMBERIAN STIMULASI CUTANEUS DAN VIRGIN COCONUT OIL (VCO) PADA PASIEN GAGAL GINJAL KRONIK DI RSU DHARMA YADNYA DENPASAR - Putu Intan Daryaswanti; Komang Agus Jerry Widyanata; Ni Made Diah Pusparini Pendet (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2021)
Background: Patients with Chronic Renal Failure undergoing Hemodialysis (HD) have various health problems, one of which is skin manifestations. Dry skin is described in the majority of patients with Renal Failure and is suspected to be a significant pathogenic factor in pruritus and may increase itching intensity in CRF patients. It was found that 52% of patients who underwent HD had dry skin (xerosis). Dry skin that appears in CRF patients with hemodialysis is usually caused by atrophy of the sebaceous glands, impaired external secretory function, and impaired hydration of the stratum corneum. Purpose: to increase skin moisture in patients with chronic renal failure undergoing hemodialysis Methods: This community service is carried out by providing VCO and teaching massage stroking techniques. VCO is applied to the skin twice a day for 4 weeks followed by massage. Results: Of the 53 patients, 60.37% of patients experienced an increase in skin moisture, 16.98% of patients had a decrease in skin moisture levels and 22.64% could not be evaluated Conclusion: Routinely apply VCO twice a day for 4 weeks, experience an increase in the value of skin moisture. Meanwhile, in patients who did not apply regularly, there was a slight increase compared to patients who did not apply VCO at all. Oily skin and the smell of coconut oil are the reasons for patients not to routinely give VCO.